Strategic Entrepreneurship: The Role of Human Resource Practice and it Capabilities in Managing Performance Firm - Irianina, Bella; Nasution, Yasmine (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
In order to realize Corporate Entrepreneurship (CE), the context of Human Capability and successful strategic alignment of IT with business strategy, companies must coordinate components such as: business strategy, IT strategy and HRM strategy. Business performance measures the contribution of the business and technology domains to the company's business objectives. Both the company's external and internal environment affect the company's performance. The novelty of the research is to explain the role of human resource practice and it capabilities in managing performance firm. This study examines the impact of corporate of entrepreneurship on performance, whether directly and indirectly through dynamic capability and the direct impact dynamic capability has on performance. This research uses Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. Data is collected from 100 business units from divisions that are directly related to measurement variables, namely Information & Technology, Human Resources and Operations in several industrial pillars in Indonesia. The findings highlight that technology has a direct impact on corporate entrepreneurship because the progress of the times makes every industry player need to implement technology for data integration. And Human Resources also has a direct impact on Corporate Entrepreneurship where every organization needs to implement Strategic Human Resources to assist employees in hire to retire activities. These two variables are also assisted by dynamic capability, so that each individual or platform used has followed the applicable rules, thus leading to Learning Growth and Internal Business Processes in good performance.